Transient Bone Marrow Hypoplasia Preceding T-Cell Acute Lymphoblastic Leukemia: a case report - Naturinda, Ernest; Ssenyondwa, Joseph; Bakulumpagi, Deogratias; Lubega, Joseph; Wasswa, Peter (African Health Sciences, 2021)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy and is characterised by hy- perproliferation of malignant lymphocytes in the bone marrow. Rarely, ALL may be preceded by a period of pancytopenia and bone marrow hypoplasia which spontaneously recovers. This phenomenon, which has not before been described in T-cell ALL, is referred to as transient bone marrow hypoplasia. A 5-year-old boy who presented with high-grade fever and generalised lymphadenopathy, was found to have pancytopenia on peripheral blood count and bone marrow hypoplasia. He was observed over a one-month period during which his bone marrow and peripheral blood counts recovered spontaneously. Symptoms recurred after 4 months and he was found to have blast infiltration of the bone marrow and diagnosed with T-cell ALL. Cases of transient bone marrow hypoplasia or overt aplastic anemia with spontaneous recovery and then followed by B-cell ALL or Acute Myeloid Leukemia have been described previously in the medical literature. This is the first case of transient bone marrow hypoplasia resulting into ALL of T-cell immunophenotype. While marrow hypoplasia preceding ALL remains poorly understood, it suggests an antecedent environmental insult to lymphoid progenitors or a germline abnormality that predisposes to lymphoid dysplasia. This may provide clues to the hitherto unknown pathophysi- ological process and etiological factors that precede the majority of childhood ALL cases. This case enlightens pediatricians about the existence of such rare cases so as to periodically follow up children with pancytopenia and/or bone marrow hy- poplasia for prolonged periods even after apparent recovery.